INTEGRASI HUKUM ISLAM PADA MASA ORDE BARU - Mhd. Khadafi Abdullah; Asasriwarni Asasriwarni; Ikhwan Matondang (Ensiklopedia of Journal, 2026)
Islamic law in Indonesia experienced significant development during the New Order era, when the government began integrating various aspects of Islamic law into the national legal system despite maintaining restrictions on Islamic political activities. This integration was realized through the enactment of several important regulations, such as Law Number 14 of 1970 on the Basic Provisions of Judicial Power, Law Number 1 of 1974 on Marriage, Government Regulation Number 28 of 1977 on the Endowment of Owned Land, Law Number 7 of 1989 on Religious Courts, and Presidential Instruction Number 1 of 1991 on the Compilation of Islamic Law. These regulations demonstrate that Islamic law was no longer merely a moral religious norm but had gained legitimacy as an integral part of Indonesia’s positive legal system.This study employs a library research method with a descriptive qualitative approach. Data were collected from literature, journals, statutory documents, and scholarly opinions, then analyzed qualitatively to describe the processes, policies, and dynamics of Islamic law integration during the New Order era. The findings indicate that the integration of Islamic law in this period was pragmatic and state-controlled, with Islamic legal provisions accommodated as long as they supported national stability and development agendas. Nevertheless, this era became an essential foundation for the advancement of Islamic law in Indonesia, particularly in strengthening religious courts, codifying family law, and structuring national endowment (waqf) administration.Keywords: Islamic Law, New Order, Legal Integration, Religious Courts, Compilation of Islamic Law